2015
DOI: 10.1111/mec.13150
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of a migratory divide reveals candidate genes for migration and implicates selective sweeps in generating islands of differentiation

Abstract: Differential gene flow, reductions in diversity following linked selection and/or features of the genome can structure patterns of genomic differentiation during the process of speciation. Possible sources of reproductive isolation are well studied between coastal and inland subspecies groups of Swainson's thrushes, with differences in seasonal migratory behaviour likely playing a key role in reducing hybrid fitness. We assembled and annotated a draft reference genome for this species and generated whole-genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(155 citation statements)
references
References 85 publications
8
146
1
Order By: Relevance
“…Highly divergent genomic regions do not necessarily coincide with regions of reduced gene flow among established or emerging species. Several alternative interpretations exist for the numerous high-F ST regions we detected in all pairwise comparisons (Cruickshank & Hahn, 2014;Delmore et al, 2015;Nachman & Payseur, 2012;Noor & Bennett, 2009). Nevertheless, careful examination of these outliers of differentiation may reveal significant insights into the wide range of genes and traits that contribute to ecological divergence and/or reproductive isolation between subgroups of An.…”
Section: Genomic Architecture Of Geographic and Reproductive Isolationmentioning
confidence: 88%
“…Highly divergent genomic regions do not necessarily coincide with regions of reduced gene flow among established or emerging species. Several alternative interpretations exist for the numerous high-F ST regions we detected in all pairwise comparisons (Cruickshank & Hahn, 2014;Delmore et al, 2015;Nachman & Payseur, 2012;Noor & Bennett, 2009). Nevertheless, careful examination of these outliers of differentiation may reveal significant insights into the wide range of genes and traits that contribute to ecological divergence and/or reproductive isolation between subgroups of An.…”
Section: Genomic Architecture Of Geographic and Reproductive Isolationmentioning
confidence: 88%
“…Genomic analyses of contact zones between other Corvus subspecies (cornix, corone, orientalis and pectoralis) revealed clustering of certain pigmentation genes, albeit in different genomic islands (Vijay et al 2016). Other studies, however, have shown that genes potentially involved in reproductive isolation do not always cluster together, instead they are scattered across the genome (Parchman et al 2013;Ruegg et al 2014; but see Delmore et al 2015). These contrasting findingscandidate 'speciation genes' clustered in genomic islands versus scattered throughout the genome-suggests that the genetic basis of speciation is highly species-specific and context-dependent.…”
Section: Exploring the Genomic Landscapementioning
confidence: 99%
“…Cathartus ustulatus (subspecies) GBS Migration, plumage, and song (−) Ruegg et al (2014) WGS Migration (+) Delmore et al (2015) Anas platyrhynchos GBS Lavretsky et al (2015) Anas diazi 4 species of Ficedula WGS Burri et al (2015) Corvus corone WGS Plumage coloration (+) Poelstra et al (2014) (subspecies) WGS Plumage coloration (+) Vijay et al (2016) 16 species of Darwin's finches WGS Bill morphology (+) Lamichhaney et al (2015) Sphyrapicus nuchalis GBS Grossen et al (2016) Sphyrapicus ruber…”
Section: Manacus Vitellinusmentioning
confidence: 99%
“…By studying the secondary contact hybrid zones closely, we may investigate if there are any barriers to gene flow between the taxa involved and combine that with information about potential forces behind divergence, that is if taxa have diverged because of random acquisition of incompatibility alleles (observed trait differences not related to ecology) or if adaptation has played a major role in the divergence process (potential trait differences clearly associated with ecology) (Toews & Irwin, 2008). In addition, studying secondary contact zones can give information about the designation of lineages with unclear taxonomic status by allowing for quantification of genetic differentiation and potential introgression between involved taxa (Abbott et al., 2016; Delmore et al., 2015; Payseur & Rieseberg, 2016). …”
Section: Introductionmentioning
confidence: 99%